Internet chat based intervention as a mode for therapy and counselling - Jini K Gopinath; Marsha Rodrigues; Puneet Manuja (Cambridge Prisms: Global Mental Health)
Increasing mental health issues in India demands for a strong intervention to curb the rise. According to the World Health Organization, roughly around 21 Indians out of 100,000 die by suicide every year. The burden on mental health domain increases due to the existing system as most of the existing services follow a traditional approach and are most sought after but lack reachability and ease of access. This study recognises the need for programmes that help in reachability and ease of access while simultaneously maintaining anonymity, therefore, analyses the impact of chat-based therapy provided online through the platform. The paper analyses the difference in subjective unit of well-being (SUW) pre and post chat-based sessions among 2624 college students and 805 corporate employees. The Wilcoxon signed rank test between pre and post intervention indicates significant results with the p < 0.001 (Z = −44.100a) suggesting and increase in SUW scores post intervention. Further, the Kruskal–Wallis test revealed that the gender of the clients has an association with the SUW scores (p < 0.05). It was also found that the duration of the sessions had a positive relation with the impact scores (p < 0.001).